Access of non‐residents to transplantation of deceased donor organs: practices and strategies in the European setting. (20th October 2021) - Pérez‐Blanco, Alicia; López‐Fraga, Marta; Forsythe, John; Pires Silva, Ana M.; Cardillo, Massimo; Novotná, Petra; Tullius, Stefan G.; Cozzi, Emanuele; Ashkenazi, Tamar; Delmonico, Francis L.; Domínguez‐Gil, Beatriz; ,; et al.
Summary: The access of non‐resident patients to the deceased donor waiting list (DDWL) poses different challenges. The European Committee on Organ Transplantation of the Council of Europe (CD‐P‐TO) has studied this phenomenon in the European setting. A questionnaire was circulated among the Council of Europe member states to inquire about the criteria applied for non‐residents to access their DDWL. Information was compiled from 28 countries. Less than 1% of recipients of deceased donor organs were non‐residents. Two countries never allow non‐residents to access the DDWL, four allow access without restrictions and 22 only under specific conditions. Of those, most give access to non‐resident patients already in their jurisdictions who are in a situation of vulnerability (urgent life‐threatening conditions). In addition, patients may be given access: (i) after assessment by a specific committee (four countries); (ii) within the framework of official cooperation agreements (15 countries); and (iii) after patients have officially lived in the country for a minimum length of time (eight countries). The ethical and legal implications of these policies are discussed. Countries should collect accurate information about residency status of waitlisted patients. Transparent criteria for the access of non‐residents to DDWL should be clearly defined at national level. Abstract : The access of non‐resident patients to the deceased donor waiting list (DDWL) poses different challenges. This study shows the different policies in place in the European setting and discuss its ethical and legal implications.